Comparison of time curves from dynamic 18F-fluciclovine positron emission tomography and dynamic contrast-enhanced magnetic resonance imaging for primary prostate carcinomas - Andreas Julius Tulipan; Ljiljana Vlatkovic; Eirik Malinen; Bjørn Brennhovd; Knut Håkon Hole; Agnes Kathrine Lie; Harald Bull Ragnum; Mona-Elisabeth Revheim; Therese Seierstad (Physics and Imaging in Radiation Oncology, 2018)
Background and purpose: Multimodal imaging is increasingly included in the assessment of prostate cancer patients, and there is a need to study whether different techniques provide similar or complementary information. In the initial perfusion phase contrast agents and radioactive labelled tracers act as blood-pool agents and may show similar characteristics. The purpose of the current work was to compare time-activity- and time-concentration-curves (TCs) of dynamic 18F-fluciclovine (18F-anti-1-amino-2-[F]-fluorocyclobutane-1-carboxylic acid, FACBC) positron emission tomography (PET) and dynamic contrast-enhanced magnetic resonance imaging (DCE MRI). Materials and methods: Dynamic FACBC PET and DCE MRI were performed on 22 patients with intermediate or high-risk prostate cancer within 23 days prior to robot-assisted laparoscopic prostatectomy. Index tumour was delineated in the images using whole mount tissue sections as reference standard. Tumour TCs from PET and MRI were compared visually and quantitatively by calculating correlation coefficients between the curves at different time points after injection. Results: For the first minute post injection, the mean correlation coefficient between the TCs from PET and MRI was 0.92 (range; 0.75–0.99). After the first minute, MRI showed washout while PET showed plateau kinetics. Conclusion: Dynamic FACBC and DCE MRI showed similar wash-in time curve characteristics. At later time points, FACBC plateaued whereas MR contrast medium washed out. In DCE MRI, the usefulness of wash-in information is well documented. Whether wash-in information from dynamic FACBC can provide added value remains to be documented. Keywords: Prostate carcinoma, Fluciclovine, FACBC, MRI, Uptake characteristics